Pesticide Risk Behavior and Knowledge of Chili and Tomato Farmers. Issue 4 (3rd July 2016) - Praneetvatakul, Suwanna; Schreinemachers, Pepijn; Laitae, Chaniga
ABSTRACT: Intensification of agricultural land use in developing countries is coincident with increased use of synthetic pesticides, which could lead to misuse and overuse. For measures to reduce risk from pesticides to be effective, it is necessary to understand farmers' rationale for pesticide use. This study was undertaken to analyze the relationship between pesticide use and farmers' risk behavior and knowledge of pesticide risk. Data were gathered from 200 Thai farmers growing hot (chili) pepper ( Capsicum annuum L) and tomato ( Solanum lycopersicum L). Pesticide risk knowledge was measured using a pesticide risk beliefs inventory. Risk behavior was measured with farmers making pesticide use decisions under hypothetical situations. Farmers were highly risk averse because they preferred to incur a high cost of pesticides to quickly eliminate pest problems. Regression analysis indicated that pesticide use is positively associated with lower levels of pesticide knowledge and higher levels of risk aversion. Enhancing farmer knowledge about pesticide risk can make an immediate contribution to lowering pesticide use.